Introduction to library public services / G. Edward Evans, Anthony J. Amodeo and Thomas L. Carter. 6th ed. Englewood, Colo.: Libraries Unlimited, 1999. XVIIII, 500 p. (Library and Information Science text series). ISBN: 1-56308-633-6 (pbk) (Información, cultura y sociedad, 2004)
Reseña.